2003
DOI: 10.2486/indhealth.41.117
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of White-Collar Jobs in Regard to Mental Health Consultation Rates in a Health Care Center Operated by a Japanese Company

Abstract: The aim of this study was to compare the consultation rates (CR) of workers performing several types of white-collar jobs. We collected data from the database inputted at the first consultation to a health care center from April 1996 to March 1999. We found that the CR of engineer group was 2.3 times higher than that of employees involved in research and development group. We speculate that this is partially due to the portion, which is not small, of computer systems engineer (SE) comprising this group; SE has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Specifically, Hämmig [ 23 ] postulated that knowledge workers were more likely to have mental health problems compared to manual workers due to the severe psychosocial nature of their jobs. Other studies found work-related stress influenced the mental health of certain occupations, and that high levels of occupational stress were detrimental to the mental health of workers in those occupations [ 24 , 25 ]. Finally, compared to the general population, teachers [ 26 ], healthcare workers (especially nurses and physicians) [ 27 , 28 ], and civil servants [ 23 , 24 ] experienced higher occupational stress and worse psychosocial working conditions because of their job role and types of occupation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Hämmig [ 23 ] postulated that knowledge workers were more likely to have mental health problems compared to manual workers due to the severe psychosocial nature of their jobs. Other studies found work-related stress influenced the mental health of certain occupations, and that high levels of occupational stress were detrimental to the mental health of workers in those occupations [ 24 , 25 ]. Finally, compared to the general population, teachers [ 26 ], healthcare workers (especially nurses and physicians) [ 27 , 28 ], and civil servants [ 23 , 24 ] experienced higher occupational stress and worse psychosocial working conditions because of their job role and types of occupation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%